Policing belonging: race and nation in the UK - Parmar, A (Oxford University Press, 2018)
This chapter considers the impact of the police’s increased involvement in migration control. How (and with what consequences) do criminalization, migration, race, and gender intersect when the police are asked to respond to migration and fears about migrants? Drawing on empirical research on police custody suites, the piece discusses how the policing of migration questions the presence of minority ethnic groups in the UK, the wider implications for those who cannot belong, and how procedures are racialized. It also highlights the widening reach of the police, whose work is increasingly carried out in conjunction with other actors including those who have been enlisted to surveil, report, and help enforce migration policy. The chapter brings to light the everyday forms of racism renewed through the policing of migrants while exploring how those who are deemed risky, not belonging, criminal, or a threat to social and economic resources are racialized.